A new species of Brycon (Characiformes: Characidae) from Nicaragua and Costa Rica, with a key to the lower Mesoamerican species of the genus - Angulo, Arturo; Gracian-Negrete, Jatziry Marlene (Zootaxa, 2013)
A new species of Brycon is described from the Atlantic slope of Nicaragua and Costa Rica. Brycon costaricensis n. sp. differs from all other Central American Brycon species by the following combination of characters: 49 to 54 scales in the lateral line; 5 or 6 rows of scales between lateral line and pectoral fin base; 9 to 11 rows of scales between lateral line and dorsal fin base; 5 to 7 rows of scales between lateral line and anal fin base; anal fin notably longer than head, with 33 to 37 total rays; and a elongated and shallow caudal peduncle, whose length is 1.78 to 2.35 times its depth. A key to lower Mesoamerican species of the genus is also presented.